Performance effect of applying paraffin wax on solar photovoltaic backplate - E. Roslan; A. Razak (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The efficiency of solar photovoltaic (PV) panels is affected by its operating temperature. Having high irradiance produces high electrical output but also heats up the panel and reducing the panels efficiency. This study investigates the effect of cooling solar PV panels using 750g of paraffin wax as phase change material (PCM) applied to the back plate of a solar PV panel. The experiment is done at Kajang, Selangor, Malaysia. The result is reduction of up to 9.5°C, increase of up to 0.947W or 11.82% of electrical power output when compared to the panel without any PCM applied. The panel cooled with PCM also produced 4.69% more energy